Influence of ceramic material, thickness of restoration and cement layer on stress distribution of occlusal veneers - Tribst, João Paulo Mendes [UNESP]; Dal Piva, Amanda Maria de Oliveira [UNESP]; Penteado, Marcela Moreira [UNESP]; Borges, Alexandre Luiz Souto [UNESP]; Bottino, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to evaluate stress distribution in an occlusal veneer according to the restorative material, restoration thickness, and cement layer thickness. A tridimensional model of a human maxillary first molar with an occlusal veneer preparation was constructed using a modeling software of finite element analysis. The model was replicated 9 times to evaluate the factors: restoration thickness (0.6, 1.2, and 1.8 mm) and cement layer thickness (100, 200, and 300 μm). Then, each model received different restorative materials (High Translucency Zirconia - [YZHT], Lithium Disilicate - [LD], Zirconia Reinforced Lithium Silicate - [ZLS], Feldspathic - [F], and Hybrid Ceramic - [HC]), totaling forty-five groups. An axial load (600 N) was applied on the occlusal face for static structural analysis. Solids were considered isotropic, homogeneous, and linearly elastic. Contacts were considered perfectly bonded. Fixation occurred in the dental root and a mechanical static structural analysis was performed. Descriptive statistical analysis and one-way ANOVA (α =10%) were performed for tensile stress peak values in the restoration and cement layer. The difference between groups was compared using the Tukey's test with 10% significance to match the percentage of the mesh convergence test. According to the results, the cement layer thickness did not influence stress distribution in the restoration (p ≥ 0.10). The thicker the restoration, the higher the tensile stress concentration in the restoration. The graphs showed higher stress concentration in the YZHT, followed by LD, F, ZLS, and HC. Also, the restorative material influenced stress concentration on the cement layer, which decreased according to the sequence HC>YZHT>ZLS>LD>F. HC stood out for causing the least stress concentration in the restoration. Cement layer thickness did not interfere in the mechanical performance of the restorations.